EST_HydrolysisRate_versus_Desludge.csv - Brown, Gareth; Jefferson, Bruce; MacAdam, Jitka (Cranfield University, 2022)
Data outputs from matlab mass balance model for calculation of hydrolysis rate constant against desludging frequency
Keywords: wastewater'